THE IMPORTANCE OF INVESTMENT IN DISASTER RISK REDUCTION: LESSONS FROM THE GREAT EAST JAPAN EARTHQUAKE 2011 - Nadhila Adani (Jurnal Manajemen Bencana (JMB), 2022)
Japan has a long history of large-scale earthquakes causing damage or collapse of buildings, fires and tsunamis. On March 11, 2011 an earthquake occurred in East Japan with a magnitude of 9.0 striking the Tohoku region (northeast Japan), which includes Sendai City, coastal areas of Iwate, Miyagi and Fukushima prefectures. The earthquake generated a tsunami that destroyed buildings, but also claimed tens of thousands of lives. This is also likely to occur in Indonesia with a threat similar to the potential for a large earthquake from the megathrust fault in the Sunda Strait, Banten, which can have a magnitude of 8.7 which could occur at any time. Seeing one of the priority actions in the Sendai Framework for Disaster Risk Reduction (SFDRR), namely investing in disaster risk reduction (DRR), this study aims to take lessons from large-scale disasters, especially the earthquake and tsunami that occurred in East Japan in 2011 so that the Indonesian people can be resilient to disasters. This study uses a descriptive qualitative approach with the research method being a literature study from literature, e-journals, and websites. The results of this study find that funds from the central government are needed to invest in DRR capacity development for local governments through infrastructure and non-infrastructure in the pre-disaster, preparedness and post-disaster processes.